Problems Faced by Tribes in Collection and Marketing of Tendu (Diospyros melanoxylon Roxb.) Fruit in Jhalawar District of Rajasthan - Sharma, Shirish; Dadhich, Sourabh (International Journal of Economic Plants, 2025)
The present study was conducted during September to December, 2022 to focus on the problems in collection and marketing of tendu fruit by tribes in Jhalawar district of Rajasthan. This district was selected purposively because the more than 15% tribal population is residing in this district. In this study 3 blocks namely: Jhalrapatan, Aklera and Khanpur blocks were selected purposively. From each selected block 50 respondents were selected randomly thus making total sample size to 150. The result of the study show that the marketing pattern of respondents shows that the weekly market was respondents’ first choice. The majority of respondents, 86 (57.33%), were between the ages of 36 and 50, with only 44 (29.33%) between the ages of 18 and 30. Social involvement, occupation, and extent of sustainable livelihood were negative and significantly correlated at the 1% and 5% level of probability. Major source of income is non-farm activities, followed by agriculture related activities. Majority of respondents use bicycles as mode of transport, while motor bikes are used by only 26.00 % of respondents and majority of the collectors were literate. The major problem faced by respondents was lack of developed market infrastructure for Tendu fruit (94.66%) and least was lack of inexpensive storage facilities (24.66%). The majority respondents suggested that government develop the existing market infrastructure for marketing to deal with collection and marketing problem of Tendu fruit.